Statistical Science Is International – And Survey Statistics Is Cool and Hot - Kulldorff, Gunnar (Lithuanian Journal of Statistics, 2014)
The paper presents a short history of international cooperation in statistics, formation of statisticalassociations and their activities in the world and in the Nordic countries. The cooperation background for Baltic and Nordicstatisticians before 1992 is presented. The contents of the activities of the Baltic–Nordic–Ukrainian Network on SurveyStatistics is highlighted.